The Challenges and Strategies of Teachers in Teaching TOEFL and IELTS Test Preparation - Delvia Roza (J-SHMIC : Journal of English for Academic, 2019)
High-stake English proficiency tests, such as TOEFL and IELTS, open up opportunities for the people in Indonesia to study in reputable universities, both local and abroad. Since Indonesian learners are non-native English speakers, some institutions help them to overcome the problems they have with the tests. Related to these issues, the teachers may face some challenges in teaching the students who want to reach their target scores. For that reason, this study was conducted to find out: 1) teacher challenges in teaching the TOEFL and IELTS tests, and 2) teacher strategies in motivating the students. The location of the study was in an English educational institution in Pekanbaru. The participants were 10 teachers who had taught these tests preparation for more than two years. The method used was a qualitative approach with face-to-face interviews as the data collection instrument. It was found that the challenges of the teachers in teaching the tests were 1) students’ high expectations, 2) lack of effort from students, 3) study time limitations, 4) teachers’ experience, 5) issues with high school students, and 6) the number of students in a class. It was also found that the teachers’ strategies in motivating the students were 1) students’ awareness of the opportunities of passing the tests, 2) fun learning, 3) telling stories of people who are successful through passing the tests, and 4) reminding the students why they joined the class, spending much money, time and energy on these tests. All in all, though teachers faced some challenges in teaching IELTS and TOEFL tests, they also had strategies to overcome them.